The Distribution of Consumption Expenditure in Sub-Saharan Africa : The Inequality among All Africans - Jirasavetakul, La-Bhus Fah; Lakner, Christoph (World Bank, Washington, DC, 2016)
This paper uses a set of national household surveys to study the regional Sub-Saharan Africa distribution of consumption expenditure among individuals during 1993 to 2008. The analysis puts the disparities in living standards that exist among persons in Africa into context with the disparities that exist within and between African countries. Regional interpersonal inequality has increased (from a Gini index of 52 percent in 1993 to 56 percent in 2008), driven by increasing disparities in living standards across countries, while there has been no systematic increase in within-country inequality. For the African distribution as a whole, growth of consumption expenditure (from household surveys) has been low (around 1 percent per year). This growth has been uneven and as a result the richest 5 percent of Africans received around 40 percent of the total gains, while the bottom third stagnated.